Negotiating families and personal lives in the 21st century : exploring diversity, social change and inequalities - Quaid, Sheila, 1961-.; Hugman, Catriona, 1985-; Wilcock, Angela, 1963- (Oxon : Routledge, 2022)
'This is a vital new resource in the sociological study of family life in the 21st century. The chapters in this volume explore a diverse range of family and intimate life experiences, such as personal choices about reproduction and how life choices and family forms are mediated by factors including geographical location, race, ethnicity, sexuality, gender, income, and government policy'--
Includes bibliographical references and index.
Keywords: Families; Families -- History